2008
DOI: 10.1007/s10750-008-9332-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying phenotypic gradients in freshwater snails: a case study in Lithasia (Gastropoda: Pleuroceridae)

Abstract: Many authors have described a pattern of morphological variation in freshwater bivalves where shells taken from lentic and lotic environments, or headwaters and main stem reaches, appear to exhibit phenotypic gradients in size and shape. For example, mussels taken from headwater reaches tend to possess smooth, less inflated shells compared to the more obese, sculptured individuals downstream. Others observed similar relationships in certain freshwater gastropods, but this variation has not been quantified nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 50 publications
0
35
2
3
Order By: Relevance
“…In Duck River L. geniculata, we observed that smaller shells were narrower than larger shells, and that more globose shells were associated with greater discharge volumes and the presence of freshwater drum, river redhorse, and saddleback darter. Our allometric trend was opposite of that seen by Minton et al (2008), who suggested smaller shells were more globose. We feel this discrepancy may be due to sample size; we used 300 shells compared to over 1,100 shells used previously, and Minton et al (2008) used more shells of each morphotype, including many that were intermediate between forms.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In Duck River L. geniculata, we observed that smaller shells were narrower than larger shells, and that more globose shells were associated with greater discharge volumes and the presence of freshwater drum, river redhorse, and saddleback darter. Our allometric trend was opposite of that seen by Minton et al (2008), who suggested smaller shells were more globose. We feel this discrepancy may be due to sample size; we used 300 shells compared to over 1,100 shells used previously, and Minton et al (2008) used more shells of each morphotype, including many that were intermediate between forms.…”
Section: Resultscontrasting
confidence: 99%
“…Our allometric trend was opposite of that seen by Minton et al (2008), who suggested smaller shells were more globose. We feel this discrepancy may be due to sample size; we used 300 shells compared to over 1,100 shells used previously, and Minton et al (2008) used more shells of each morphotype, including many that were intermediate between forms. We feel that, taken together, the data suggest that allometry across different morphotypes may not be meaningful relative to analysing each form separately.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Os moluscos subulinídeos, como D. muibum, foram, em grande maioria, descritos com base apenas na morfologia da concha, porém nem sempre isso é possível devido às semelhanças entre espécies (choh et al, 2006) e variações entre populações de uma mesma espécie (caLDeira et al, 2000;minton et al, 2008). Estudos de variações nas medidas da concha podem resultar na constatação de diferentes padrões morfométricos, permitindo inferir sobre características do animal, como forma do corpo e padrão de crescimento (chiu et al, 2002).…”
Section: Discussionunclassified